Penyeleksian Penerimaan Teleservice Representative dengan Penerapan Metode ARAS dan Pembobotan ROC - Agus Iskandar (STMIK Budi Darma, 2023)
Company Refers to a business entity or organization established by one or several individuals with the intention of producing or selling goods or services with the aim of making a profit. In helping to increase company sales by promoting new products or services to customers and establishing better relationships with existing customers, a teleservice representative is needed. A teleservice representative is a customer service professional who works via a remote communication device such as a telephone, email or text message. . To achieve this, they must have the criteria of Experience, Good Negotiation, Communication Articulation, Interpersonal and Confidence. The presence of a Teleservice Representative is very important for the company in ensuring that the quality of customer service is continuously improved and customers are satisfied with the company's products or services. So companies must make the right selection of teleservice representatives because teleservice representatives have a very vital role for the company because they are a direct line in providing superior customer service and guaranteeing customer satisfaction. To solve problems in the selection of teleservice representatives, an information system is needed, namely a decision support system (SPK). In this study, the Additive Ratio Assessment (ARAS) method and ROC weighting are applied, which are methods that can be used to make decisions and produce values on selection weights in the selection of teleservice representatives. so that the alternative that produces the selection of teleservice representatives, which can be seen in table 10, is alternative A4, namely Nisa Fadillah with a value of 1.0000